Skrining Kesehatan dan Edukasi Kesehatan tentang Hipertensi pada Masyarakat Dukuh Karangjambe: Health Screening and Health Education on Hypertension to the Community of Karangjambe Village - Rosyidah, Rosyidah; Ansel, Muhammad Dzaki Fulvian; Peni, Nur; Suryana, Aufatcha Ayutya; Wibowo, Najwa Karina; Nasution, Novarinsa Hidayah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Hypertension is still ranked number one among the top ten diseases in Yogyakarta. Based on the Banguntapan III Health Center profile, in 2022, it was found that 568 people suffered from hypertension; this is due to the discovery of cases from research carried out by group 26 Field Learning Practices (PBL), namely the highest case of non-communicable diseases obtained was hypertension, 27 people (36%). This community service activity aims to follow up on problems related to hypertension in the Dukuh Karangjambe area. There are several stages in the method used in this community service activity. The first stage of this community service activity is the community diagnostic method used to explore problems and identify problems in the area. The service implementation time is from May 23, 2024, to July 14, 2024, with a team of 6 people: one lecturer and five students. The results of determining the priority of problems based on the community diagnosis of hypertension are problems that need to be resolved in the area. Intervention activities are carried out with several activities, namely health screening, health education, and gymnastics. The results of this counselling showed an increase in knowledge in the excellent category from before the counselling 50 and after the counselling 74.5. The Wilcoxon test's statistical results (p-value = 0.000) showed a significant difference in the average knowledge score about hypertension before and after the counselling.